Pemaknaan Gerakan Maskulin pada Ibing Pencug: Sebuah Telaah Historis - Saepudin, Asep; Yulaeliah, Ela; Burhan, Mukhammad Agus (Department of History, Faculty of Humanities, Diponegoro University, 2025)
This research has two objectives. First, it analyzes the meaning of pencug dance in relation to the artists’ history, social background, and cultural context. Second, it explores how functional art theory can be applied to study pencug performances. Pencug dance is an improvisational form performed in Karawang-style Jaipongan. It is unique because, although performed by female dancers, it exhibits a masculine character, unlike Bandung-style Jaipongan, which typically reflects feminine traits. The study employs a historical method combined with Erwin Panofsky’s iconographic-iconological approach, including field and library research (heuristics), criticism, interpretation, and historiography. The research was conducted in Karawang, West Java, using the Namin Group as the sample. The findings show that Panofsky’s theory can analyze performing arts through three stages. First, the pre-iconographic description focuses on the textual aspects of pencug dance movements, highlighting the masculine style typical of Karawang performances. Second, iconographic analysis examines themes and concepts, revealing a populist theme and a focus on improvisation and spontaneity. Third, iconological interpretation considers the symbolic meaning of pencug dance, informed by the artists’ experiences and the historical and cultural background of the Karawang community. The study concludes that the masculine character of pencug dance originates from the self-defense practices of the Karawang jawara. Historically, these warriors developed agility, combat skills, and expertise in machetes, martial arts, and Pencak Silat to respond to disturbances during the royal, colonial, and post-independence periods. These self-defense techniques later transformed into pencug dance movements, such as kepret, tajong, gunting, pasang, pukul, tendang, siku, and tangkis, which became integral to Karawang-style Jaipongan.